STAT3 inhibition in combination with CD47 blockade inhibits osteosarcoma lung metastasis - Shrestha, Pradeep; Shrestha, Rejeena; Zhou, You; Zielinski, Rafal; Priebe, Waldemar; Kleinerman, Eugenie S. (Frontiers in Immunology, 2025)
BackgroundNew therapies are urgently needed for patients with osteosarcoma (OS). STAT3 and CD47 are potential therapeutic target in OS. Here we investigated the therapeutic activity of the orally bioavailable STAT3 inhibitor, WP1066, and anti-CD47 antibody using OS mouse models.MethodsCytotoxic effect of WP1066 against OS cell lines and its immunomodulatory effects were evaluated in vitro. Experimental metastasis and orthotopic syngeneic mouse models were used to investigate the therapeutic efficacy of WP1066 and anti-CD47 antibody. Further flow cytometric analysis was performed.ResultsSTAT3 was constitutively activated in multiple human and mouse OS cell lines. WP1066 suppressed STAT3 activation and induced apoptosis. WP1066 reduced the viability and proliferation of MDSCs and increased the expression level of MHC-II, and CD80 in macrophages. We demonstrated that WP1066 monotherapy prolonged the survival of mice with OS lung metastasis using an experimental metastasis and an orthotopic model. The therapeutic effect was significantly increased when WP1066 was combined with anti-CD47. This was associated with increased frequency of activated CD8+ T cells, NK cells and macrophages in the lungs and LDLNs.ConclusionOur preclinical studies support further investigation of targeting STAT3 and CD47 as novel immunotherapeutic approach against OS lung metastasis.